PROFITABILITAS, KEPEMILIKAN INSTITUSIONAL, DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Dimas Wicaksono; Venty Sugiyanti (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
This study aims to examine the effect of profitability, institutional ownership, and company size on the timeliness of financial reporting. The population in this study is the consumer goods industry sector companies listed on the Indonesia Stock Exchange for the period 2014-2018. The sampling method used was purposive sampling method in order to obtain 12 companies. The total data processed in this study were 60 data. The type of data used is secondary data in the form of annual financial reports for companies in the consumer goods industry listed on the Indonesia Stock Exchange for the period 2014 - 2018. The data analysis method used in this study is logistic regression. The results of this study indicate that profitability has a significant negative effect on timeliness of financial report submission, institutional ownership has no significant effect on timeliness of financial report submission, and company size has a significant positive effect on timeliness of financial report submission.